Design of an aerodynamic attitude control system for a CubeSat - Auret, Jacoba (Stellenbosch : Stellenbosch University, 2012)
Thesis (MscEng)--Stellenbosch University, 2012. ENGLISH ABSTRACT: The Cape Peninsula University of Technology, in collaboration with Stellenbosch University, is developing a 3-unit CubeSat for a low earth polar orbit. The two main payloads are a camera and a radio frequency beacon. This beacon will be used to calibrate the radar antenna patterns of an antenna of the Hermanus Magnetic Observatory at their base in Antarctica. This thesis describes the development of an aerodynamic attitude determination and control system needed to achieve three-axis stabilisation of the satellite and to perform accurate pointing of the camera. The satellite structure is designed to utilise aerodynamic means of control. It includes four feather antennae for passive pitch-yaw stabilisation and two active aerodynamic roll control paddles. The sensors used are a three-axis magnetometer, ne sun sensor and nadir sensor. Three attitude determination methods are investigated, namely the Triad, Rate Kalman Filter and Extended Kalman Filter algorithm. Apart from the aerodynamic control elements of the satellite, three magnetic torque rods and three nano-reaction wheels are also included in the design. Three control modes for the satellite are identi ed and various control methods are investigated for these control modes. The various attitude determination and control methods are evaluated through simulations and the results are compared to determine the nal methods to be used by the satellite. The magnetic Rate Kalman Filter is chosen as attitude determination method to be used when the satellite is tumbling and a combination of the sun Rate Kalman Filter and the Triad algorithm is to be used when the satellite experiences low angular rates. The B-dot and Y-spin controller is chosen for the detumbling control mode, the aerodynamic and cross-product control method for the three-axis stabilisation control mode and the quaternion feedback control method for the pointing control mode of the satellite. The combination of magnetic and ...